Sterilization Pattern of Dental Clinics in Rangpur City (Bangladesh Journal of Dental Research & Education, 2013)
Objective: The purpose of the study was to collect information to assess the level of sterilization practice and to identify the method of sterilization in the dental clinics in Rangpur city for further research and evaluation of the treatment quality. The study was carried out from January 2012 to June 2012 among 25 Dental clinics in Rangpur city for 6 months period. Results: Among the Respondents (16%) said draping sheet was supplied by the authority, while in 84% were not supplied. Distribution of Respondents by wearing theater shoes in the clinic were (96%) whereas (4%) didnt wear and 52% of the patients wore theater shoes in the clinic whereas 48% didnt wear it. Among the respondents 8% said plastic syringe was used in the clinic while 92% didnt use, Dental surgeons of 72% (18) of the total clinics used to wear disposable hand gloves where 28% didnt wear, 52% (13) of the Dental surgeons used to wear apron whereas 48% didnt. Among the clinics gloves were available in 92% for the service providers and 68% apron were available for the service providers. (24%) of the respondents used dettol to wash the floor, whereas 76% used savlon. Among all the operative rooms 8% used separate container to deposit sharp and other waste and 92% didnt use.(96%) of the clinics used chlorohexidine with cetrimide (savlon), and 4% (1)used Chlorohexidine with alchohol (hibisol) ). Among all the clinics 24% used sterilized Cotton and 76% didnt and 64%  used sterilized gauge .(96%) of the clinics had availability of disinfectants. Only (4%) of the clinics had all the available sterilization methods. (96%) of the clinics had availability of surface disinfected. Only (8%) of the clinics had all the available instruments sterilizer. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16601 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 1-4